2015
DOI: 10.2174/1570159x13999150318113800
|View full text |Cite
|
Sign up to set email alerts
|

Rat Ultrasonic Vocalizations and Behavioral Neuropharmacology: From the Screening of Drugs to the Study of Disease

Abstract: Several lines of evidence indicate that rats emit ultrasonic vocalizations (USVs) in response to a wide range of stimuli that are capable of producing either euphoric (positive) or dysphoric (negative) emotional states. On these bases, recordings of USVs are extensively used in preclinical studies of affect, motivation, and social behavior. Rat USVs are sensitive to the effects of certain classes of psychoactive drugs, suggesting that emission of rat USVs can have relevance not only to neurobiology, but also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 138 publications
(187 reference statements)
2
56
1
4
Order By: Relevance
“…The resulting signal was digitalized and saved as.wav files. Temporal and frequency characteristics of 50 kHz calls were extracted using Avisoft analysis software (SAS-Lab Pro, v 4.38, Avisoft Bioacoustic, Berlin) and categorized offline into flat, step, or trill subtype, according to pattern analysis [14,47]. Flat calls had peak frequency changes ≤ 5 kHz, although the difference between start and end frequencies could be > 5 kHz if it had an upward or downward direction.…”
Section: Usvsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting signal was digitalized and saved as.wav files. Temporal and frequency characteristics of 50 kHz calls were extracted using Avisoft analysis software (SAS-Lab Pro, v 4.38, Avisoft Bioacoustic, Berlin) and categorized offline into flat, step, or trill subtype, according to pattern analysis [14,47]. Flat calls had peak frequency changes ≤ 5 kHz, although the difference between start and end frequencies could be > 5 kHz if it had an upward or downward direction.…”
Section: Usvsmentioning
confidence: 99%
“…The oxytocin-induced decrease in 40 kHz "distress" calls by maternally separated rat pups [13] was reversed by an oxytocin antagonist, suggesting involvement of this receptor. However, there are no reports of the effect of oxytocin on rat 50 kHz ultrasonic vocalizations (USVs) accompanying positive emotional states specific to reward-associated situations, which may have translational relevance to communicative deficits associated with negative symptoms in man [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Audible squeak occur during playing and fighting and during handling concurrently with struggling. Researchers must be aware that procedures that cause rats to vocalise in order to communicate stress in both sonic and ultrasonic ranges affect the behaviour and physiology of neighbouring rats within audible range, this disturbs welfare and can cause biased results 41 . Rats dislike any kind of physical restraint and usually they will alert others of by sound, ultrasound and odour, so when this is necessary like during preanaesthetic medication, it should be done away of the others.…”
Section: Vocal Communicationmentioning
confidence: 99%
“…Similarly, drug abuse research has demonstrated that certain abused drugs affect the quantity of USVs, others affect the acoustic features of USVs, and that some drugs may affect both the quantity and acoustic features of USVs (reviewed in Simola 13 and Barker et al 14 ). Finally, there is some evidence which suggests that highly salient events may preferentially elicit USVs with higher rates of modulation than events of lower salience.…”
Section: Introductionmentioning
confidence: 99%